2003
DOI: 10.1128/iai.71.9.5432-5435.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Small Nucleoid-Binding Proteins H-NS, HU, and Fis Affect hilA Expression in Salmonella enterica Serovar Typhimurium

Abstract: hilA encodes an activator of Salmonella enterica serovar Typhimurium virulence genes and is transcriptionally modulated by environmental conditions. We show that H-NS represses hilA under low-osmolarity conditions. H-NS, HU, and Fis also appear to affect the derepression of hilA by HilD. Modulation of hilA by counteracting repressing and derepressing mechanisms may allow Salmonella serovar Typhimurium to regulate its virulence genes in response to different situations in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 25 publications
1
96
0
1
Order By: Relevance
“…Some reports have established that low-osmolarity and lowtemperature conditions result in reduced hilA expression (Ono et al, 2005;Schechter et al, 2003), and others have shown that hilA expression is growth phase-dependent, being hilA-induced at the onset of the stationary phase when cells are grown in aerated LB medium (Song et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports have established that low-osmolarity and lowtemperature conditions result in reduced hilA expression (Ono et al, 2005;Schechter et al, 2003), and others have shown that hilA expression is growth phase-dependent, being hilA-induced at the onset of the stationary phase when cells are grown in aerated LB medium (Song et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Their effect seems to be indirect, as they sense osmolarity and bile/short-chain fatty acids, respectively (Altier, 2005;Ellermeier et al, 2005;Lucas & Lee, 2001). Other global regulators that positively modulate hilA expression are Fur (Ellermeier & Slauch, 2008) and the nucleoid-associated proteins Fis, HU (Schechter et al, 2003) and the bacterial IHF (Mangan et al, 2006). IHF binds to many target DNA sequences and plays a role as a transcription factor (Browning et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H-NS has been shown to repress the transcription of hilA, a number of its activators, and other horizontally acquired SPIs (38,46,48,49,53). We hypothesized that the upregulation of hns in the fur-deficient cells may explain the observed Fur-dependent expression of hilA (Fig.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…Thus, most studies have been carried out using bacteria grown under so-called inducing conditions, namely high osmolarity and low oxygen conditions (LB containing 0.3 M NaCl without aeration). Studies of bacteria grown under these conditions have, to date, revealed that hilA expression is regulated by a complex array of regulatory systems including hilC/sirC/sprA (13)(14)(15), hilD (15), sirA/barA (16,17), fis (18,19), csrAB (16,20), envZ/ ompR (21), phoB (7), fadD (7), fliZ (7), hha (22), H-NS (19), and HU (19). Two of these genes, hilC and hilD, encode AraC-like transcriptional activators that activate hilA transcription by binding upstream of the hilA promoter DNA (15,23,24).…”
mentioning
confidence: 99%